CYTOTOXIC AND ANTIBACTERIİAL ACTIİVITY OF THE MIXTURE OF OLIVE OIL AND LIME CREAM IN VITRO CONDITIONS - Sumer, Zeynep; Yildirim, Gulay; Sumer, Haldun; YÄ±ldÄ±rÄ±m, Sahin (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The mixture of olive oil and lime cream has been traditionally used to treat external burns in the region of Hatay/Antakya and middle Anatolia. Olive oil and lime cream have been employed by many physicians to treat in many ailments in the past. A limited number of studies have shown the antibacterial effect of olive oil and that it does not have any toxic effect on the skin. But we did not find any reported studies on the mixture of olive oil and lime cream. The aim of this paper is to investigate the cytotoxic and antibacterial activity of olive oil and lime cream individually or/and in combination in vitro conditions, by using disk-diffusion method and in cell culture. The main purpose in using this mixture is usually to clear burns without a trace. Agar overlay, MTT (Cytotoxicity assay) and antibacterial susceptibility tests were used to investigate the cytotoxic and antibacterial activity of olive oil and lime cream. We found that lime cream has an antibacterial activity but also cytotoxic on the fibroblasts. On the other hand olive oil has limited or no antibacterial effect and it has little or no cytotoxic on the fibroblasts. When we combined lime cream and olive oil, olive oil reduced its cytotoxic impact. These results suggest that mixture of olive oil and lime cream is not cytotoxic and has antimicrobial activity.The mixture of olive oil and lime cream has been traditionally used to treat external burns in the region of Hatay/Antakya and middle Anatolia. Olive oil and lime cream have been employed by many physicians to treat in many ailments in the past. A limited number of studies have shown the antibacterial effect of olive oil and that it does not have any toxic effect on the skin. But we did not find any reported studies on the mixture of olive oil and lime cream. The aim of this paper is to investigate the cytotoxic and antibacterial activity of olive oil and lime cream individually or/and in combination in vitro conditions, by using disk-diffusion method and in cell culture. The main purpose in using this mixture is usually to clear burns without a trace. Agar overlay, MTT (Cytotoxicity assay) and antibacterial susceptibility tests were used to investigate the cytotoxic and antibacterial activity of olive oil and lime cream. We found that lime cream has an antibacterial activity but also cytotoxic on the fibroblasts. On the other hand olive oil has limited or no antibacterial effect and it has little or no cytotoxic on the fibroblasts. When we combined lime cream and olive oil, olive oil reduced its cytotoxic impact. These results suggest that mixture of olive oil and lime cream is not cytotoxic and has antimicrobial activity.